Ecological spirituality : cross cultural perspective - National Seminar on "Ecology and Religion: Ecological Spirituality in Cross Cultural Perspective" (2006 : St. Aloysius College, Jabalpur); George, Davis, 1950-; Aloysian Explore and Worship Forum; St. Aloysius College (Jabalpur, India); Metanexus Institute (New Delhi : Serials Publications, 2007)
Contributed seminar papers presented at the seminar organized by Aloysian Explore and Worship Forum in collaboration with the Metanexus Institute, Philadelphia.
Includes bibliographical references.
Keywords: Ecology -- Religious aspects -- Christianity -- Congresses; Religious pluralism -- India -- Congresses; Religion and science -- Congresses; Theology, Doctrinal -- India -- Congresses